Significance of Human Development, Labor Participation, and Unemployment in Driving Regional Economic Growth - Al Berto, Muhammad; Al-farisy , Muhammad Daffa (International Ecsis Association, 2025)
East Java Province stands as the second largest contributor to Indonesia’s economy, driven by its strong industrial, trade, and agricultural sectors. However, disparities in human development and labor market dynamics persist across regions. This study aims to investigate the effects of the Human Development Index (HDI), Labor Force Participation Rate (LFPR), and Open Unemployment Rate (OUR) on regional economic growth in East Java during 2017–2023. Using panel data regression from 38 regencies/cities and applying the Common Effect Model with robust standard errors, the findings reveal that HDI positively and significantly influences economic growth, reflecting the pivotal role of human capital. In contrast, LFPR and OUR both show significant negative effects, suggesting that labor participation without quality employment and high unemployment undermine economic performance. These results imply that merely increasing labor participation is insufficient without parallel improvements in job quality, economic diversification, and workforce productivity. The study contributes to regional development literature by highlighting the nuanced interplay between human development and labor market indicators. The findings offer valuable insights for policymakers to prioritize inclusive human resource development, reduce unemployment, and enhance the quality of labor market absorption to foster sustainable economic growth.